OP0164 Blockade of Immune Complex-Mediated Glomerulonephritis by Highly Selective Inhibition of Bruton's Tyrosine Kinase. (15th July 2016) - Chalmers, S.A.; Doerner, J.; Bosanac, T.; Khalil, S.; Smith, D.; Harcken, C.; Dimock, J.; Der, E.; Herlitz, L.; Webb, D.; Seccareccia, E.; Feng, D.; et al.
Abstract : Background: Lupus nephritis (LN) causes significant morbidity and mortality in SLE patients. Autoantibody-containing immune complexes (ICs) can activate complement cascades and Fc receptors on resident and infiltrating cells within the kidney, thus promoting inflammation. Bruton's tyrosine kinase (BTK) is a tyrosine kinase important for B cell development, Fc receptor signaling, and macrophage polarization. Objectives: To assess the role of BTK in the pathogenesis of nephritis in an inducible model of LN, and to evaluate the therapeutic potential of BTK inhibition. Methods: A novel, highly selective, and potent (mouse whole blood CD69 IC50 =13±2 nM) BTK inhibitor, BI-BTK-1 (Boehringer Ingelheim), was tested in female 129 sv/J mice (10 weeks of age) injected with nephrotoxic serum (NTS), an experimental model which closely mimics LN. Mice pre-immunized with rabbit IgG (Day 0) were administered NTS containing rabbit anti-mouse glomerular antibodies (Day 5), inducing a severe IC-mediated crescentic glomerulonephritis. Mice that did not receive the NTS transfer were used as healthy controls. Mice were treated once daily with vehicle alone or BI-BTK-1 (0.3–10 mg/kg, n=16/group), before the transfer of NTS as a prophylactic assessment, or after the transfer of NTS as a therapeutic assessment. Results: NTS-challenged mice treated with BI-BTK-1 exhibited a statistically significant, dose responsive protection from kidney disease. Compared to vehicle treated mice, NTS-challenged mice treated with 10 mg/kg BI-BTK-1 had significantly less proteinuria (1220 mg/dl vs 10 mg/dl, respectively, p<0.0005), serum creatinine (0.74 mg/dl vs 0.48 mg/dl, respectively, p<0.03), and BUN (82 mg/dl vs 25 mg/dl, respectively, p<0.03) at the end of study (Day 11). Histology assessment confirmed marked renal protection in the BI-BTK-1 treatment groups. BI-BTK-1 treatment resulted in decreased recruitment of inflammatory monocytes from the splenic reservoir, and a decrease in infiltrating IBA-1+ cells as well as C3 deposition within the kidney. RNA-seq revealed that more than 500 genes were modulated by BTK treatment, with further analysis highlighting many of the modulated pathways being related to inflammation and glomerular injury in LN. Serum profiling and selective kidney gene expression analyses by Q-PCR revealed that BTK inhibition was associated with a significant decrease in the levels of key LN-relevant inflammatory cytokines and chemokines. Importantly, delayed treatment with 3 mg/kg of BI-BTK-1in mice with established proteinuria was able to reverse proteinuria and improve renal histopathology. Conclusions: Our results further confirm the important role for BTK activation in the pathogenesis of immune complex-mediated nephritis, and highlight BTK as a valuable therapeutic target. Taken together with previously published studies and our preliminary results in spontaneous lupus models, these findings further strengthen the rationale for selective BTK inhibition as a promising approach to the treatment of LN. Disclosure of Interest: S. Chalmers: None declared, J. Doerner: None declared, T. Bosanac Employee of: Boehringer Ingelheim, S. Khalil Employee of: Boehringer Ingelheim, D. Smith Employee of: Boehringer Ingelheim, C. Harcken Employee of: Boehringer Ingelheim, J. Dimock Employee of: Boehringer Ingelheim, E. Der: None declared, L. Herlitz: None declared, D. Webb Employee of: Boehringer Ingelheim, E. Seccareccia Employee of: Boehringer Ingelheim, D. Feng Employee of: Boehringer Ingelheim, J. Fine Employee of: Boehringer Ingelheim, M. Ramanujam Employee of: Boehringer Ingelheim, E. Klein Employee of: Boehringer Ingelheim, C. Putterman Grant/research support from: Boehringer Ingelheim